Associação da ocorrência de formigas (Hymenoptera: Formicidae) com atributos do solo e da vegetação em um domínio do cerrado à nordeste do estado do maranhão, Brasil - Silva, Edison Fernandes da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Ants live in tree tops and shrubs, with many species using the soil/litter interface for foraging and other are resident in the soils. In this study proposes to identify species of ants in an area of the Cerrado Northeastern State of Maranhao and correlate the occurrence of ants with attributes of soils, vegetation, moisture and temperature at ground level. The study was conducted in the municipality of Chapadinha-MA in six environments: E1 and E2 Typical Dystrophic Oxisol, E3 Entisol Typical Dystrophic, E4 Petroplíntico Dystrophic Oxisol, E5 Paludalf Dystrophic Ultisol and E6 Plinthosol Petrico Êndico Litoplíntico. The characterization of the vegetation was carried out by phytosociological survey in 40 x 40 m plots. To evaluate the physical and chemical properties of the soils we collected disturbed soil samples and preserved structure in 0,0 - 0,1 m, 0,1 - 0,2 m and 0,2 - 0.3 m layers. The ants were collected with protein and a carbohydrate baits (sardines and honey) using nine pairs of baits distributed in the 40 x 40 m plots from six environments. To collect the ants in each plot the baits were observed individually for one hour (08:00 and 11:00 am) and the ants who accessed the baits were monitored and collected directly at the entrance of their nests. The dry biomass of litter was obtained in 1 m2 plots randomly distributed in 40 x 40 m plots. Humidity and temperature were obtained with hygrometer placed directly on the soil surface from the sampling environments. Descriptive statistical analysis and Principal Component Analysis (PCA) was carried out in the physical and chemical soil attributes. Ten ant species with higher importance value (HIV) were used in the PCA analysis. These species were correlated with soil attributes, litter biomass, basal area, humidity and temperature at ground level. Forty eight species from 7 subfamilies and 24 genera have been found. Nine species were restricted to records environments: E1 and ...

As formigas ocupam dosséis de árvores e arbustos, com muitas espécies utilizando a interface solo/serapilheira para forrageamento e outras com hábito residente nos solos. Nesse trabalho se propôs identificar espécies de formigas em um domínio de Cerrado à Nordeste do Estado do Maranhão e correlacionar a ocorrência das formigas com atributos dos solos, da vegetação, da umidade e temperatura ao nível do solo. O trabalho foi realizado no município de Chapadinha – MA em seis ambientes: A1 e A2 LATOSSOLO AMARELO Distrófico típico, A3 NEOSSOLO FLÚVICO Distrófico típico, A4 LATOSSOLO AMARELO Distrófico petroplíntico, A5 ARGISSOLO ACINZENTADO Distrófico arênico e A6 PLINTOSSOLO PÉTRICO Litoplíntico êndico. A caracterização da cobertura vegetal foi realizada a partir levantamento fitossociológico em parcelas de 40 x 40 m. Nessas parcelas foram coletadas amostras de solo deformadas e com estrutura preservada nas camadas 0,0 – 0,1 m, 0,1 – 0,2 m e 0,2 – 0,3 m para caracterização física e química. As formigas foram coletadas em cada ambiente com auxílio de iscas proteicas e carboidráticas (sardinha e mel). Nove conjuntos de iscas foram distribuídas em uma malha amostral quadrada (40 x 40 m) e a distância entre as iscas foi de dez metros uma da outra. Cada isca foi monitorada individualmente, por um período de 1 hora, entre 08:00 às 11:00 horas. As formigas que acessaram as iscas foram acompanhadas e coletadas diretamente na entrada dos respectivos formigueiros. A biomassa seca de serapilheira foi obtida em parcelas de 1 m2 distribuídas aleatoriamente nas parcelas de 40 x 40 m. As medidas de umidade e temperatura foram obtidas com auxílio de termohigrômetro posicionado diretamente na superfície do solo dos ambientes de amostragem. Os atributos físicos e químicos do solo receberam tratamento estatístico descritivo e foram usados nas correlações multivariadas, utilizando análise de componentes ...
Keywords: Solos; Cerrados; Físico-química do solo; Formiga; Analise multivariada; Maranhão (MA); Ants